Video-bandwidth impact and compensation in wideband high-efficiency power amplifiers - Barros, Diogo Rafael Bento (2022)
The aim of this work is to determine, quantify and model the performance degradation of wideband power amplifiers when subject to concurrent multiband excitation, with a particular focus on the average efficiency variation. The origins of this degradation are traced to two main transistor properties: the output baseband current generation by the nonlinear transconductance, and the input baseband current generation by the nonlinear gate-source capacitance variation. Each mechanism is analised separately, first by providing a qualitative and intuitive explanation of the processes that lead to the observed efficiency degradation, and then by deriving models that allow the prediction of the average efficiency dependence with the input signal bandwidth. The resulting knowledge was used to improve matching network design, in order to optimize baseband impedance terminations and prevent the efficiency degradation. The derived models were experimentally validated with several PA prototypes implemented with Gallium Nitride HEMT devices, using both conventional and optimized baseband impedance matching networks, achieving over 400MHz instantaneous bandwidth with uncompromised efficiency. The consolidation of the wideband degradation mechanisms described in this work are an important step for modelling and design of wideband, high-efficiency power amplifiers in current and future concurrent multi-band communication systems.